Manajemen Kelas Masa Pasca Pandemi Covid-19 - Karmilah Karmilah (Universitas Negeri Malang, 2023)
Abstract: The aim of research on Post-Pandemic Classroom Management is to understand howteachers can manage their classrooms effectively after facing the challenges and changes caused by the COVID-19 pandemic. This study aims to provide information and ad vice to teach-ers on how best to address the current situation and optimize student learning experiences. Themethod that can be used in this research is Literature Study: Literature re search on classroommanagement and the impact of the pandemic on education. This includes reading scientific articles, books, and journals related to classroom management and the COVID-19 pandemic. This article discusses proper classroom management in the post-pan demic period. The COVID-19 pandemic has affected education around the world, including classroom management. Goodclassroom management is essential in creating a safe and pro ductive learning environment forstudents. This article providesseveralsuggestions and strat egies to help teachers manage theirclassrooms effectively in a post-pandemic situation, in cluding strategies for building a positiveclassroom climate, managing student behavior, de veloping social and emotional skills, and building technology skills. It is hoped that with this article, teachers can obtain useful infor- mation and advice in managing their classrooms during the post-pandemic period, so as to create a safe, positive and productive learning environment for students.Keywords: Management, Pandemic, Covid-19Abstrak: Tujuan dari penelitian mengenai Manajemen Kelas Masa Pasca Pandemi adalah untuk memahami bagaimana guru dapat mengelola kelas mereka dengan efektif setelah menghadapi tantangan dan perubahan yang disebabkan oleh pandemi COVID-19. Penelitian ini bertujuan untuk memberikan informasi dan saran kepada guru tentang cara terbaik untuk mengatasi situasi saat ini dan mengoptimalkan pengalaman belajar siswa. Metode yang dapat digunakan dalam penelitian ini adalah Studi Literatur: Penelitian literatur tentang manajemen kelas dan dampak pandemi pada pendidikan. Hal ini meliputi membaca artikel ilmiah, buku, dan jurnal terkait manajemen kelas dan juga pandemi COVID-19. Artikel ini membahas tentangmanajemen kelas yang tepat dalam masa pasca pandemi. Pandemi COVID-19 telah mempengaruhi pendidikan di seluruh dunia, termasuk manajemen kelas. Manajemen kelas yang baik sangat penting dalam menciptakan lingkungan belajar yang aman dan produktif bagisiswa. Artikel ini memberikan beberapa saran dan strategi untuk membantu guru mengelola kelas mereka dengan efektif dalam situasi pasca pandemi, termasuk strategi untuk membangun iklim kelas yang positif, mengelola perilaku siswa, mengembangkan keterampilan sosial dan emosional, dan membangun keterampilan teknologi. Diharapkan dengan adanya artikel ini, guru dapat memperoleh informasi dan saran yang berguna dalam mengelola kelas mereka padamasa pasca pandemi, sehingga dapat menciptakan lingkungan belajar yang aman, positif, dan produktif bagi siswa.Kata kunci: Manajemen, Pandemi, Covid-19